National Identity in Literary Translation - Kieltyka, Robert; Barcinski, Lukasz (Studies in Linguistics, Anglophone Literatures and Cultures, 2020)
This book offers a wide selection of carefully selected studies examining some of the most compelling issues, which have been explored in the area of literary translation. The contributions were authored by an international group of scholars who focused on the recent developments in the field, encompassing the complex aspects of cultural transfer; translation of stylistic devices; and the importance of convention and ideology. However, the most distinctive feature of this book is that it offers a multifaceted view of the condition of the contemporary national identities and its linguistic transfer from different perspectives within various source language/target language pairs.